ISLAMIC EDUCATION IN TWO THOUGHT POLES: AN ANALYSIS OF THE IDEAS OF KH. HASYIM ASY’ARI AND KH. AHMAD DAHLAN - Fathonah, Enden Siti Nur; Sahudi, Sahudi; Sejati, Cakra Sastra Sukma; Mulyadi, Yadi; Mukhsin, Mukhsin (FAJAR Jurnal Pendidikan Islam, 2025)
The purpose of this study is to compare the concepts of Islamic education from the perspectives of KH. Hasyim Asy'ari and KH. Ahmad Dahlan. This study uses a qualitative method with a literature review. The collected data are analyzed descriptively. This study concludes that KH. Hasyim Asy'ari is known for his pesantren education model, which emphasizes the deepening of religious knowledge and character building, while KH. Ahmad Dahlan pioneered the integration of religious and general knowledge through the modern madrasah system. Pesantren and madrasah are two main educational models that complement each other in shaping a generation of Muslims who are knowledgeable, have good character, and are ready to face the challenges of the times. The integration of religious and general knowledge is the key to creating holistic Islamic education that is relevant to the needs of modern society. NU plays a role in preserving classical Islamic scholarly traditions through pesantren and madrasah diniyah, while Muhammadiyah develops modern education that adapts to the times without neglecting Islamic values. The educational concepts and practices proposed by these two figures have become important pillars in national development, making Islamic education in Indonesia adaptive, inclusive, and rooted in Islamic values. The contributions of NU and Muhammadiyah to contemporary Islamic education are highly significant in addressing the challenges of the times. By combining the strength of traditional scholarship with modern innovation, both organizations have created a holistic, adaptive model of Islamic education that is oriented toward Islamic values and 21st-century competencies. Their synergy must continue to be strengthened to shape a moderate, competitive Muslim generation ready to face the era of globalization.